Comparative study of SnS recrystallization in molten CdI2, SnCl2and KI. Issue 1 (29th October 2015) - Timmo, Kristi; Kauk‐Kuusik, Marit; Pilvet, Maris; Mikli, Valdek; Kärber, Erki; Raadik, Taavi; Leinemann, Inga; Altosaar, Mare; Raudoja, Jaan
Abstract: In the present study, the recrystallization of polycrystalline SnS in different molten salts CdI2, SnCl2 and KI as flux materials are presented. The recrystallization and growth of polycrystalline material in molten salts produces unique SnS monograin powders usable in monograin layer solar cells. XRD and Raman analysis revealed that single phase SnS powder can be obtained in KI at 740 °C and in SnCl2 at 500 °C. Long time heating of SnS in molten CdI2 was accompanied by chemical interaction between SnS and CdI2 that resulted in a mixture of CdS and Sn2 S3 crystals. SEM images showed that morphology of crystals can be controlled by the nature of the flux materials: needle‐like Sn2 S3 together with round edged crystals of CdS in CdI2, flat crystals of SnS with smooth surfaces in SnCl2 and well‐formed SnS crystals with rounded edges in KI had been formed. The temperatures of phase transitions and/or the interactions of SnS and flux materials were determined by differential thermal analysis. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)